1995
DOI: 10.1103/physrevb.51.7834
|View full text |Cite
|
Sign up to set email alerts
|

L-subshell fluorescence yields for metallic uranium and thorium

Abstract: The L x-ray spectra induced by -50-keV electron impact on metallic targets of uranium and thorium have been analyzed and the relative fluorescence yields of the L&, L2, and L3 subshell of the two elements, cu2/~3 and co&/~"have been derived. The present values of co2/~3 and co2 are notably different

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…At high lattice temperature and/or high excitation levels, the relation becomes 34 P T ϳ(ប LO /)exp(Ϫប LO /k B T e ) with the effective hotelectron relaxation time. The practical evaluation of electron temperature as a function of input power complicates the numerical calculation considerably, 29 and I do not attempt it in the present paper. As for a theoretical study I take the electron temperature (T e ) as an input parameter in the calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At high lattice temperature and/or high excitation levels, the relation becomes 34 P T ϳ(ប LO /)exp(Ϫប LO /k B T e ) with the effective hotelectron relaxation time. The practical evaluation of electron temperature as a function of input power complicates the numerical calculation considerably, 29 and I do not attempt it in the present paper. As for a theoretical study I take the electron temperature (T e ) as an input parameter in the calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from experimental 14 and theoretical 29 studies have indicated that the power signals detected in phonon emission experiments can be described by the electron energy loss rate ͑EELR͒ induced by electron-phonon interaction. The hot-electron energy loss problem in 2DSS's has been investigated rather extensively.…”
Section: A Electron Energy Loss Ratementioning
confidence: 99%
“…We did not include the effects of electron-electron (e-e) screening within our calculations. The theoretical results reported have shown that at relatively high temperatures ͑and/or high-electron temperatures͒ the influence of the e-e screening on the transport properties ͑e.g., electron mobility, 10,20 magnetoresistivities, 9 and electron energy loss 21 ͒ is rather weak. This is because the inclusion of e-e screening through, e.g., random phase approximation results in an enhancement of the effective rate of electron scattering due to dynamical effects and in a reduction of the density of states by static screening over the entire temperature and electron density region.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature control is often achieved using Peltier plates and transformation thermotics. [ 9–15 ] However, the application is limited by factors such as energy consumption, complicated structure design, and bulkiness. Ultrathin metal‐dielectric nanostructures with high absorption have been proposed for broadband infrared camouflage.…”
Section: Introductionmentioning
confidence: 99%